Geotechnical engineering calculations and rules of thumb - Rajapakse, Ruwan (Elsevier/Butterworth-Heinemann, 2008)
Geotechnical Engineering Calculations Manual offers geotechnical, civil and structural engineers a concise, easy-to-understand approach the formulas and calculation methods used in of soil and geotechnical engineering. A one stop guide to the foundation design, pile foundation design, earth retaining structures, soil stabilization techniques and computer software, this book places calculations for almost all aspects of geotechnical engineering at your finger tips. In this book, theories is explained in a nutshell and then the calculation is presented and solved in an illustrated, step-by-step fashion. All calculations are provided in both fps and SI units. The manual includes topics such as shallow foundations, deep foundations, earth retaining structures, rock mechanics and tunnelling. In this book, the author's done all the heavy number-crunching for you, so you get instant, ready-to-apply data on activities such as: hard ground tunnelling, soft ground tunnelling, reinforced earth retaining walls, geotechnical aspects of wetland mitigation and geotechnical aspects of landfill design. .Easy-to-understand approach the formulas and calculations .Covers calculations for foundation, earthworks and/or pavement subgrades .Provides common codes for working with computer software .All calculations are provided in both US and SI units.
Keywords: Engineering geology -- Mathematics -- Handbooks, manuals, etc.; Soil mechanics -- Mathematics -- Handbooks, manuals, etc.; elektronické knihy; electronic books